La discapacidad intelectual grave en los jóvenes del Área Inclusión Hogar de la Unidad Educativa Especializada de El Oro y su incidencia en la comunicación intrafamiliar. Periodo lectivo 2014-2015. Machala – Ecuador. - Barrete Pérez, Diana Carolina (2015)
The present research is aimed at a vulnerable sector are families with a young man with severe intellectual disabilities , those who struggle every day to get better communication with your children even though they often do not speak and only media either through sounds, signals , gestures or body language. These families will be considered in this research to help them improve the quality of life of their children and avoid family conflicts due to lack of proper communication.